SELF-IMAGE OF THE FIRST-YEAR STUDENTS OF TECHNICAL UNIVERSITY - A. Avdeeva; Yu. Safonova (Вестник университета)
This article describes the current issues of studying self-image of students of elite technical university. The first-year students have been involved in the study. The cognitive and emotional components of self-image were selected as the subject of the study. Diagnostic research complex included interview methods, questioning, observation, analysis of documents and the author’s projective drawing technique «I am a student». According to the results of the empirical research, 1) such five types of images, as elitism, cognition, integration, difficulties, forcedness have been highlighted; 2) the interpretation of self-image of first-year students by the type of drawing has been carried out.